Effects of substrate color on intraspecific body color variation in the toad‐headed lizard, Phrynocephalus versicolor. Issue 18 (15th August 2019) - Tong, Haojie; Li, Jiasheng; Wo, Yubin; Shao, Gang; Zhao, Wei; Aguilar‐Gómez, Diana; Jin, Yuanting
Abstract: Diversity in animal coloration is generally associated with adaptation to their living habitats, ranging from territorial display and sexual selection to predation or predation avoidance, and thermoregulation. However, the mechanism underlying color variation in toad‐headed Phrynocephalus lizards remains poorly understood. In this study, we investigated the population color variation of Phrynocephalus versicolor . We found that lizards distributed in dark substrate have darker dorsal coloration (melanic lizards) than populations living in light substrates. This characteristic may improve their camouflage effectiveness. A reciprocal substrate translocation experiment was conducted to clarify the potential role of morphological adaptation and physiological plasticity of this variation. Spectrometry technology and digital photography were used to quantify the color variation of the above‐mentioned melanic and nonmelanic P. versicolor populations and their native substrate. Additionally, substrate color preference in both populations was investigated with choice experiments. Our results indicate that the melanic and nonmelanic populations with remarkable habitat color difference were significantly different on measured reflectance, luminance, and RGB values. Twenty‐four hours, 30 days, and 60 days of substrate translocation treatment had little effects on dorsal color change. We also found that melanic lizards choose to live in dark substrate, while nonmelanic lizards have no preference for substrate color. In conclusion, our results support that the dorsal coloration of P. versicolor, associated with substrate color, is likely a morphological adaptation rather than phenotypic plasticity. Abstract : Melanic and nonmelanic populations with remarkable habitat color difference were significantly different on measured reflectance, luminance, and RGB values. Substrate translocation treatment had little effects on dorsal color change. Melanic lizards choose to live in dark substrate, while nonmelanic lizards have no preference for substrate color.